Adapting History Education for the 21st Century: Integrating Technology and Critical Thinking Skills - Lee, Bih Ni (Universitas Ahmad Dahlan, 2023)
Background: In the 21st century, the field of education is undergoing significant transformations due to advancements in technology and the growing emphasis on critical thinking skills. Adapting history education to meet the needs of this digital era requires integrating technology into instructional practices while fostering critical thinking abilities.This approach allows students to engage with primary sources, explore diverse perspectives, and develop the analytical skills necessary for understanding and interpreting complex historical events. Contribution: The integration of technology and critical thinking skills in history education contributes to a more dynamic and engaging learning experience for students in the 21st century. It empowers students to access primary sources, analyze multiple perspectives, and develop the essential skills needed for critical analysis and interpretation of historical events. Method: The synthesis method is a comprehensive approach to analyzing and integrating research findings on adapting history education for the 21st century through the integration of technology and critical thinking skills. By systematically reviewing and synthesizing relevant studies, it allows for the identification of common themes, trends, and gaps in the literature, providing a cohesive and nuanced understanding of the topic and informing best practices for educators in this field.. Results: The results of integrating technology and critical thinking skills in history education show improved student engagement, motivation, and understanding of historical concepts. Students also develop enhanced critical thinking abilities, such as analyzing evidence, evaluating sources, and constructing well-reasoned arguments, which prepare them for active participation in the complexities of the 21st century